2012
DOI: 10.1016/j.apgeochem.2012.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pH and temperature on the early stage of mica alteration

Abstract: a b s t r a c tMineral dissolution and precipitation reactions actively participate in controlling fluid chemistry during water-rock interaction. In this study, the changes in the biotite and muscovite basal surface nano-morphology were evaluated during interaction with fluids of different pH (pH = 1.1, 3.3 and 5.7) at different temperatures (T = 25°, 120°, and 200°C). Results show that at the nanometre scale resolution of the atomic force microscope (AFM), dissolution generates etch pits with a stair-shaped p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 25 publications
(28 reference statements)
3
32
1
Order By: Relevance
“…However, the release of Si and Al in the framework of biotite differed from that of K (Maslova et al, 2005;Pachana et al, 2012). Release rates of Si and Al with pH 4.0 citrate solution treatment were increased by 0.2 and 1.2 times, respectively, of the corresponding aqueous solution,.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…However, the release of Si and Al in the framework of biotite differed from that of K (Maslova et al, 2005;Pachana et al, 2012). Release rates of Si and Al with pH 4.0 citrate solution treatment were increased by 0.2 and 1.2 times, respectively, of the corresponding aqueous solution,.…”
Section: Discussionmentioning
confidence: 93%
“…In the presence of H + ions, aluminosilicate reacts according to the equation: Al 2 Si 2 O 5 (OH) 4 + 6H + = 2Al 3+ + 2H 4-SiO 4 + H 2 O (Kalinowski and Schweda, 1996); therefore, the coating was speculated to be an amorphous Si-bearing mineral (Shao et al, 2011;Teng et al, 2001;White and Brantley, 1995). Through the clues from boron (B) isotopes in biotite, researchers found that when pH > 4.0, the transformation rate of biotite was significantly greater than the dissolution rate of biotite (Voinot et al, 2013), namely, in a closed and steady environment, the growth of nucleation was relatively effortless on the solid-liquid interface (Pachana et al, 2012).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Oelkers et al (2008) gave an overview on the steady-state muscovite dissolution rates at temperatures from 60 to 201°C and 1 B pH B 10.3 as a function of reactive solution K, Si, and Al concentration. The findings of Pachana et al (2012) in analyzing the dissolution generates etch in the surface of biotite and muscovite basal at different pH values (pH 1.1, 3.3, and 5.7) and different temperatures (T = 2.5, 120, and 200°C) were very important, as he concluded that dissolution regime changes with pH values and temperatures. Skopljak and Vlahović (2012) wrote about the genesis of mineral waters in Kiseljak surroundings, and pointed out that the water origin from atmospheric and water descends in the primary aquifer where it becomes enriched with CO 2 and minerals.…”
Section: Introductionmentioning
confidence: 96%
“…Key factors influencing water-rock interaction include temperature, pH, pressure, catalysis, and rock characteristics (Gérard et al 2002;Oelkers et al 2008;Gysi and Stefánsson 2011;Pachana et al 2012). Gérard et al (2002) investigated the relationships between Si concentration, soil temperature, and H ?…”
Section: Introductionmentioning
confidence: 99%